The preparation and properties of three types of microcapsules of sweet orange oil using alginate and chitosan as wall material. (25th August 2014) - Xiao, Zuobing; He, Long; Zhu, Guangyong
ABSTRACT A microcapsule of sweet orange oil was prepared by the gelation of sodium alginate with Ca2+. Orthogonal experiments were designed to investigate the encapsulation efficiency (EE) to be adopted as the target index. The optimum conditions were obtained as follows: sodium alginate concentration 2% (w/v), CaCl2 concentration 1.5% (w/v), ratio of core material to wall material 1.5:1, and emulsifying agents 0.1% (w/v) Tween80 and 0.1% (w/v) glyceryl monostearate. Under these conditions, the highest EE was 76.1%. Chitosan was added to prepare chitosan‐coated calcium alginate (CCCA) and chitosan–calcium alginate complex (CCAC) gel beads. The influence of the addition of chitosan on microcapsule's morphology, EE and release characteristic was the focus of study. For these three types of microcapsules, the results showed that both surface smoothness and EE in descending order were CCAC, CCCA and calcium alginate (CA) gel beads, while the order of release rate was CA, CCCA and CCAC gel beads. These three types of microcapsules could be used in chewing gum, puffed food and other food products to control release and prevent volatilization of flavour because of their different characteristics or properties. Copyright © 2014 John Wiley & Sons, Ltd.